Multiplex detection of miRNAs based on aggregation-induced emission luminogen encoded microspheres. Issue 68 (4th December 2019) - Zou, Dan; Wu, Weijie; Zhang, Jingpu; Ma, Qiang; Fan, Sisi; Cheng, Jin; Li, Dan; Niu, Jiaqi; Qian, Xiaoqing; Li, Wanwan; Cui, Daxiang
Abstract : A miRNA multiplex detection assay based on aggregation-induced emission luminogen encoded microspheres. Abstract : Herein, we report a multiplex detection platform based on a suspension array with aggregation-induced emission luminogen (AIEgen) barcodes for simultaneous quantitative measurement of let-7b-5p, miR-16-5p and miR-19b-3p, which are associated with gastric cancer. A detection strategy by using a flow cytometer is proposed, which utilizes AIEgen-encoded microspheres to quantify the target miRNAs, and phycoerythrin as a fluorescence reporter on the detection probes to provide quantitative signals. This multiplex assay shows good specificity for recognizing single base mismatch, and possesses excellent sensitivity with limits of detection (LODs) ranging from 0.43 to 0.76 nM for the three miRNAs. The approach could be extended to the simultaneous detection of more target miRNAs by designing specific detection probes and increasing the number of fluorescence barcodes. We could foresee it holding great potential in future laboratory research and clinical applications due to its flexibility, strong multiplexed ability and good detection performance.